Youth, Inequality and Social Change in the Global South - Cuervo, Hernan; Miranda, Ana.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book gathers international and interdisciplinary work on youth studies from the Global South, exploring issues such as continuity and change in youth transitions from education to work; contemporary debates on the impact of mobility, marginalization and violence on young lives; how digital technologies shape youth experiences; and how different institutions, cultures and structures generate a diversity of experiences of what it means to be young. The book is divided into four broad thematic sections: (a) Education, work and social structure; (b) Identity and belonging; (c) Place, mobilities and marginalization; and (d) Power, social conflict and new forms of political participation of youth.
Chapter 1: Youth in the Global South: Transitions, Diversity & Inequality -- Chapter 2: Beyond the Nizam: Youth political practices in Egypt and Tunisia after the 2011 uprisings -- Chapter 3: Place, mobility and youth transitions in Indonesia -- Chapter 4: Youth, violence and subjectivities: art as resource and bond -- Chapter 5: Youth engagement In Jerusalem: Between the Palestinian youth organizations development strategies and the Israeli colonial policies -- Chapter 6: Young people's constitutional submissions in Fiji: opportunities and challenges -- Chapter 7: Intergenerational Transmission of Poverty: Exploring Subjective Well-Being, Hurdles, Risks, Shocks, and Resilience Amongst Youth in India -- Chapter 8: Social Class Reproduction amongst upper middle class in Mexico -- Chapter 9: Femininity in Everyday Life: Experiences of Malay and Indian Women in Malaysia.
Keywords: Social structure; Equality; Sociology; Social groups; Youth -- Social life and customs; Education and state; Philosophy; Postcolonialism; Social Structure; Sociology of Family, Youth and Aging; Youth Culture; Education Policy; Postcolonial Philosophy